Assessment of Doctor-Patient Communication Skills Omdurman Friendship Teaching Hospital(OFTH) August-2010 - Ahmedana, Sara Elsheikh; Mansour, Musa Basheer (Jour Med Resh and Health Sci, 2019)
Communication is the procedure of generation, transmission, or gathering of messages to oneself or another substance, for the most part by means of a commonly comprehended arrangement of signs. Communication skills are the tools that individuals use to evacuate boundaries and troubles to perform successful correspondence (are learnable, trainable, versatile simply like some other expertise). The objective was to assess the effectiveness of communication skills system among consultants, physicians, registrars and medical officers with their patients in different units of medicine and surgery. Methods: It was a descriptive-analytical study in OFTH August 2010. (241) participants by simple random sampling. All patients attend the OFTH for their appointment and agreed to be included in this study. Whereas the emergent and urgent were excluded. Data were collected using small groups discussion and pre-tested questionnaires. Results: Many doctors know some information about Doctor-Patient Communication Skills but, they didn’t perform it because of, the high frequency of patients in referral clinics. Doctors spent 6 to 10 minutes with 179 patients (74.3%), 11to 15 minutes with 46 patients (19.1%), 1 to 5 minutes with 12 patients (5%), 16 to 20 minutes with 3 patients (1.2%) and more than 26 minutes with one patient (O.4%). Patients’ satisfaction; 205 patients are satisfied represent (85.1%), 36 patients aren’t satisfied represent (14.9%). Those who aren’t satisfied; 25 patients (69%) because of a short duration of medical interview, 8 patients (22%) because doctors didn’t mention the adverse effects of the drugs and 3 patients (9%) because doctors didn’t mention the possible complications of operation. Conclusion: Doctor-patient communication skills were done by medical officers, registrars, physicians and consultants. They took a short time 6-10 minutes for medical interview (74.3%), they didn’t share information with their colleagues in the same unit by (46.5%) in 112 patients and didn’t involve other health care professionals in patients’ care by (62.7%) for 151 patients. Despite of that the patients’ satisfaction was (85.1%)